Surgical Scar Endometriosis: A Painful Scar (Medicine Today, 2025)
Introduction: A variant of extrapelvic endometriosis known as "surgical scar endometriosis" is defined by the development of functional endometrial glands and stroma close to the site of incision in individuals who have had prior surgery. As Cesarean sections have grown more popular in recent years, surgical scar endometriosis has been on the rise. The purpose of this study is to characterize surgical scar endometriosis's clinical features and management. Materials and Methods: This cross-sectional, observational study was carried out in a tertiary care center within the Obstetrics and Gynecology department of Bangabandhu Sheikh Mujib Medical University for two years, from July 2022 to June 2024. This study was designed for six women who underwent surgery for scar endometriosis. The study's objectives were to examine the general features as well as the lesions of the patients. The general features consist of mode of delivery, symptoms, ultrasound images, age and parity. The patient's lesion features, such as the size and location of the scar endometriosis (SE), the layers involved, and the surgical procedure, have been documented from the surgical notes included in the case sheet. Result: We found 6 cases of scar endometriosis in two years. The mean age of the patient was 30.7 years (range 27-36). All patients were parous women and majority (83.3%) had delivered through cesarean section, with just one had developed scar endometriosis after total abdominal hysterectomy. Here, cyclical pain and swelling at the scar site are the most typical first symptoms. In 66.7% of patients, the time between the diagnosis of surgical scar endometriosis and surgery exceeded two years. Subcutaneous tissue (100%) was the most often affected layer in surgical scar endometriosis, followed by the rectus sheath (66.7%). The preferred treatment strategy for this problem is wide local excision with or without reconstruction. Conclusions: Cesarean section is a clear risk factor for surgical scar endometriosis. Clinicians should be cautious about surgical scar endometriosis in patients who come with cyclic pain at the scar site. Scar endometriosis may be accurately diagnosed with ultrasound. The preferred therapy is surgical management with extensive local excision with a clear margin, with or without mesh repair. Precautions during obstetrical surgery to minimize wound infection can help lower the prevalence of scar endometriosis.Medicine Today 2025, Vol.37 (1): 69-72